Cortical dynamics of disfluency in adults who stutter - Sengupta, R.; Shah, S.; Loucks, T. M. J.; Pelczarski, Kristin; Scott Yaruss, J.; Gore, K.; Nasir, S. M. (My University, 2017)
Stuttering is a disorder of speech production whose origins have been traced to the central nervous system. One of the factors that may underlie stuttering is aberrant neural miscommunication within the speech motor network. It is thus argued that disfluency (any interruption in the forward flow of speech) in adults who stutter (AWS) could be associated with anomalous cortical dynamics. Aberrant brain activity has been demonstrated in AWS in the absence of overt disfluency, but recording neural activity during disfluency is more challenging. The paradigm adopted here took an important step that involved overt reading of long and complex speech tokens under continuous EEG recording. Anomalies in cortical dynamics preceding disfluency were assessed by subtracting out neural activity for fluent utterances from their disfluent counterparts. Differences in EEG spectral power involving alpha, beta, and gamma bands, as well as anomalies in phase-coherence involving the gamma band, were observed prior to the production of the disfluent utterances. These findings provide novel evidence for compromised cortical dynamics that directly precede disfluency in AWS. © 2017 The Authors. Physiological Reports published by Wiley Periodicals, Inc. on behalf of The Physiological Society and the American Physiological Society.
Citation: Sengupta, R., Shah, S., Loucks, T. M. J., Pelczarski, K., Scott Yaruss, J., Gore, K., & Nasir, S. M. (2017). Cortical dynamics of disfluency in adults who stutter. Physiological Reports, 5(9). doi:10.14814/phy2.13194
Keywords: Disfluent Speech; Neural Oscillations; Phase Coherence; Stuttering